STUDI LIVING HADIS: FILANTROPI LEMBAGA SWADAYA MASYARAKAT FORUM BINA INSAN LAMPUNG - Andi (Wahana Islamika: Jurnal Studi Keislaman, 2021)
As the second source of Islamic teachings, the hadith must always be read, interpreted and practised by Muslims. One of the social practices carried out by the Muslim community is the form of a nongovernmental organization. Therefore, this paper seeks to explore the idea of establishing a Non-Governmental Organization Community Development Forum and all its activities. This study uses the living hadith paradigm, which is how the teachings of the prophet Muhammad (peace be upon him) are transmitted practically in society. This paper concludes that; first, the social activities of a particular person or institution are often realized with the awareness to carry out religious obligation. Likewise, the Community Development Forum institution which establishes and carries out all activities of its institution is based on an understanding of the teachings of Islam, especially the second source of Islamic teachings, namely the hadith of the Prophet Muhammad. Second, the Prophet's teachings would be more easily accepted by the public if they were conveyed in deeds. Third, this research shows the teachings of Islam, especially the sunnah of the Prophet Muhammad. It can be more easily accepted in society if it is packaged in a more contemporary, united, and well-organized form.